Decision Support System for Major Determination in Madrasah Aliyah - Qonitat, Ihda Imroatun; Muhsina, Elvanisa Ayu; Uyun, Shofwatul (IJID (International Journal on Informatics for Development), 2013)
During this time, process of major determination in MAN Gondangrejo is based on value, interests, and the results of psychological tests. Interest derived from questionnaires, which gathered information about student interest on a particular subject. While the results of psychological tests are only taken from the results of the largest majors, so the decision is less than the maximum. It is because the results ignore other majors. There is no consideration of class quota of each major. Therefore, to obtain the right decision, this senior high school needs a decision support system that can help the team as the decision maker to determine of students majoring in accordance with the values, interests, intelligence / IQ, personality and skills of students. Moreover, it considers also the class quota of each major. One of application logic fuzzy is support system with Fuzzy Inference System (FIS) Mamdani. There are four stages to get output in FIS Mamdani: formation of a collection of fuzzy, formation of rules, application of function of implications and rules of inferences, and defuzzyfication. The method for developing system that used in this research is waterfall method. There are 5 steps to developing system. They are required analysis of system, interface design of system, implementation of system, testing of system and maintenance of system. This system is capable to display the rank of recommendation to all students for x class based on FIS Mamdani. The ranks are sorted from the highest to the lowest recommendation and quota of majors. This system is useful to give the right determination for majoring in senior high schools. Based on the result of system testing, 100% major decision makers in MAN Gondangrejo totally agree about this decision support system.